KESALAHAN KONSEP MATERI STOIKIOMETRI YANG DIALAMI SISWA SMA - Sri Winarni; Ade Ismayani; Fitriani Fitriani (Jurnal Ilmiah Didaktika, 2013)
Misconceptions in stoichiometry of senior high school students grade X were studied through a qualitative research using a diagnostic test in the form of multiple choices with reason on 22 students from grade X-3. The validity of the instrument found was 83%. Meanwhile the realiability found was 0,61. The misconceptions found were in: (a) reaction equation is the equality number of coefficient in reactant and in the product for about 13,63%; (b) index number of an atom in a compound is the same as in free element for about 9,09%; (c) the molecule symbol of element in the form of gass has 2 index number for about 27,27%; (d) the greater number of coefficient reaction shows the greater number of substances involved in a reaction for about 9,09%; (e) no matter how many mols in a compound, it has a fixed molecules, 6,2 x 1023 molecules, for about 4,54%; (f) define atom the same as molecules, for about 9,09%; and (g) for P and T that have the same comparison of gass volume that involves in a reaction serves as the smallest coefficient.